4‐amino‐6‐alkyloxy‐2‐alkylthiopyrimidine derivatives as novel non‐nucleoside agonists for the adenosine A1 receptor. (11th July 2016) - Cosimelli, Barbara; Greco, Giovanni; Laneri, Sonia; Novellino, Ettore; Sacchi, Antonia; Trincavelli, Maria Letizia; Giacomelli, Chiara; Taliani, Sabrina; Da Settimo, Federico; Martini, Claudia
Abstract : Three 4‐amino‐6‐alkyloxy‐2‐alkylthiopyrimidine derivatives (4 –6 ) were investigated as potential non‐nucleoside agonists at human adenosine receptors (ARs). When tested in competition binding experiments, these compounds exhibited low micromolar affinity ( K i values comprised between 1.2 and 1.9 μ m ) for the A1 AR and no appreciable affinity for the A2A and A3 ARs. Evaluation of their efficacy profiles by measurement of intracellular cAMP levels revealed that4 and5 behave as non‐nucleoside agonists of the A1 AR with EC50 values of 0.47 and 0.87 μ m, respectively. No clear concentration‐response curves could be instead obtained for6, probably because this compound modulates one or more additional targets, thus masking the putative effects exerted by its activation of A1 AR. The three compounds were not able to modulate A2B AR‐mediated cAMP accumulation induced by the non‐selective AR agonist NECA, thus demonstrating no affinity toward this receptor. Abstract : We describe the biological characterization of two novel non‐nucleoside agonists of the human A1 adenosine receptor. The two compounds are 4‐amino‐6‐alkyloxy‐2‐ alkylthiopyrimidine derivatives provided with submicromolar potency at the target receptor and high selectivity versus A2A, A2B and A3 adenosine receptors.